impedance method for force measurements - Kwah, Aloysius Boon Jin (2016)
An impedance method (IM) was developed to measure real time response to loading of a piezoceramic sample. This correlation can be applied in the design of a force sensor incorporated into a pair of surgical forceps to reduce chance of unintended tissue damage due to over clamping. The piezoceramic was tested with an Agilent 4294A Precision Impedance Analyser (IA) to determine its modes of vibrations. Next, loads were applied from 0N to 5N to illustrate the changes in the impedance plot. Plots obtained using IM were compared those of IA. Finally, load was applied to illustrate linear relationship between load and impedance change at different driving frequencies. Addition of interface material between load and piezoceramic was also explored to determine its effect. IA allowed the identification of the transverse, radial and thickness mode resonance frequencies, which coincided with those calculated empirically. Loading test done with the impedance analyser showed that an increase in loading cause an impedance increase at the resonance (trough) and a decrease at the anti-resonance (peak). Plot varies with time, suggesting a time varying impedance component. A resonance shift was detected with loading. Plots using IM coincided with those from IA, validating its effectiveness and accuracy. Linearity plots of loading responses at both resonance (!" = 0.94) and anti-resonance !" = 0.969 of thickness mode, proving that both can be used as driving frequencies. Adding of elastomeric interface could have damped out vibrations and aid force transmission, thus improving !" to 0.98. Therefore, IM proved capable of quantifying load change through impedance measurements achieving linearity of (!" = 0.98) when driven at anti-resonance frequency. Linearity improved with addition of elastomer layer. Further research can be conducted to refine this method.